High prevalence of vitamin D deficiency among pregnant women in a Turkish population and impact on perinatal outcomes. (10th October 2014) - Aydogmus, Serpil; Kelekci, Sefa; Aydogmus, Huseyin; Eriş, Serenat; Desdicioğlu, Raziye; Yilmaz, Bulent; Sağlam, Gülcan
Abstract: Objective : Maternal vitamin D deficiency is a major public health problem. The aim of this study is to investigate the influence of vitamin D deficiency on perinatal results in primigravida. Methods : One-hundred fifty-two healthy nullipar women were included in the study. Pregnant women with serum vitamin D levels <15ng/ml were defined as Group I and ≥15 ng/dl were defined as Group II; data were evaluated retrospectively. Type of delivery, gestational age at birth, birth weight, intensive care of the newborn, peri-and postpartum complications were recorded. Statistical analyses were performed with SPSS for Windows (version 16.0 ). Categorical variables were assessed using chi-squared test. The numeric variables were analyzed using Student's t -test and one-way ANOVA. Results : 44.6% of pregnant women were found to have vitamin D deficiency. The mean serum vitamin D levels for Groups I and II were 10.8 ± 3.8 and 23.8 ± 13.3 ng/ml, respectively. SGA deliveries were detected in 16.66% and 4.87% of the primigravidas with and without vitamin D deficiency, respectively. Conclusions : This study has shown that maternal vitamin D deficiency is related with an increased risk of SGA delivery. Further studies are needed to explain the relationship with vitamin D deficiency and poor perinatal outcomes.